New Insights into Drug Reaction with Eosinophilia and Systemic Symptoms Pathophysiology - Musette, Philippe; Janela, Baptiste (Frontiers in Medicine, 2017)
Drug reaction with eosinophilia and systemic symptoms (DRESS), also known as drug-induced hypersensitivity syndrome, is a severe type of cutaneous drug-induced eruption. DRESS may be a difficult disease to diagnose since the symptoms mimic those of cutaneous and systemic infectious pathologies and can appear up to 3 months after the initial culprit drug exposure. The symptoms of DRESS syndrome include rash development after a minimum of 3 weeks after the onset of a new medication, associated with facial edema, lymphadenopathy, and fever. Biological findings include liver abnormalities, leukocytosis, eosinophilia, atypical lymphocytosis, and reactivation of certain human herpes viruses. In DRESS, liver, kidneys, and lungs are frequently involved in disease evolution. Patients with serious systemic involvement are treated with oral corticosteroids, and full recovery is achieved in the majority of cases. DRESS is a rare disease, and little is known about factors that predict its occurrence. The key features of this reaction are eosinophil involvement, the role of the culprit drug, and virus reactivation that trigger an inappropriate systemic immune response in DRESS patients. Interestingly, it was evidenced that at-risk individuals within a genetically restricted population shared a particular HLA loci. In this respect, a limited number of well-known drugs were able to induce DRESS. This review describes the up-to-date advances in our understanding of the pathogenesis of DRESS.